THE INFLUENCE OF SOCIAL MEDIA INFORMATION ON GREEN CONSUMPTION ON GENERATION Z THROUGH SUBJECTIVE NORMS - Pradiva, Muhammad Sadam; Arafah, Willy (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
AbstractThis study aims to analyze the influence of social media information on green consumption among Generation Z in Jakarta, with subjective norms as a mediating variable. A quantitative approach was employed, collecting data from 300 respondents through a survey. The results indicate a significant positive relationship between social media information and green consumption, as well as between social media information and subjective norms. However, subjective norms failed to mediate the relationship between social media information and green consumption. These findings highlight the importance of social media as an information source in influencing green consumption behavior, despite the unproven role of subjective norms as a mediator. The study's implications provide insights for marketers and policymakers to enhance the effectiveness of green campaigns through social media.Keywords: Social Media Information (SOS), Green Consumption, Subjective Norms (SBN), Green Growth, Sustainable Development, Stimulus-Organisme-Respon (SOR).